2007
DOI: 10.1038/sj.bjc.6603629
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of reproductive and hormonal factors and renal cell cancer risk in women

Abstract: We examined the association of reproductive and hormonal factors with renal cell cancer risk in a cohort study of 89 835 Canadian women. Compared with nulliparous women, parous women were at increased risk (hazard ratio (HR) 1.78, 95% confidence interval (CI) 1.02 -3.09), and there was a significant gradient of risk with increasing levels of parity: relative to nulliparous women, women who had X5 pregnancies lasting 4 months or more had a 2.4-fold risk (HR ¼ 2.41, 95% CI ¼ 1.27 -4.59, P for trend 0.01). Ever u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 27 publications
5
74
0
3
Order By: Relevance
“…17,18 By contrast, only 1 cohort study found a nonsignificant direct association with age at menarche. 19 With regard to age at menopause or menopausal status, our results confirm previous null findings. [14][15][16][17][18]20 We do not confirm earlier suggestions of a relation between parity and RCC risk.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…17,18 By contrast, only 1 cohort study found a nonsignificant direct association with age at menarche. 19 With regard to age at menopause or menopausal status, our results confirm previous null findings. [14][15][16][17][18]20 We do not confirm earlier suggestions of a relation between parity and RCC risk.…”
Section: Discussionsupporting
confidence: 82%
“…15,16,18 Findings from the present study indicate a decreasing RCC risk for increasing age at first birth, in agreement with previous studies that found significant, 14,15,21 or nonsignificant inverse associations. 17,19,23 Recent longitudinal studies conducted in the United States among 37,440 women 20 and in Canada among 89,835 women 19 did not find a statistical significant association between OC use and RCC risk overall; however, when the analysis was stratified according to smoking status, OC use appeared to confer a 45% reduction in RCC risk among never smokers. 19 This reduction was in agreement with findings of 2 case-control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either tamoxifen or dihydrotestosterone (DHT) prevented the rise in cathepsin D and estrogen receptor content observed after estrogen treatment alone (89). Numerous in vitro studies have suggested the possibility that potentially reactive intermediates of estrogen may be the causative factors contributing to renal cell injury during chronic and prolonged exposure to estrogen (18,90). Estrogen-mediated cytotoxicity were confirmed in various tissues including kidney following chronic estrogen treatment (27).…”
Section: Functional Cell Biologymentioning
confidence: 96%
“…Moreover, high parity was shown to be associated with an increased risk of ccRCC, while oral contraceptive use was associated with a reduced risk. women with 5 or more births had a 2-fold increase in ccRCC risk when compared to those with 1 or 2 births (18). Some clinical studies concluded that due to significant gender differences, the occurrence of RCC will be twice as common in men as in women, for whom it will vary after the cessation of gonadal activity.…”
Section: Hormone Signaling Pathways As Treatment Targets In Renal Celmentioning
confidence: 99%